2018
DOI: 10.1080/08820139.2018.1458106
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphisms of FAS and FASL Genes and Risk of Idiopathic Aplastic Anemia

Abstract: FAS/FASL signaling system plays a vital role in the regulation of apoptosis, envisaged as a death process required for immune surveillance to prevent autoimmunity and tumorigenesis along with several other biological activities. Several single-nucleotide polymorphisms (SNPs) of FAS/FASL system can result in aberrant apoptosis, which can cause different cancers and autoimmune diseases. Aplastic anemia (AA) is an autoimmune dysfunction characterized by peripheral blood pancytopenia associated with hypoplasia of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Case 4 carried both AA-risky and -protective HLA alleles, whereas Case 11 (i.e., the patient suffering a hepatitis-associated AA subtype) only carried AA-protective alleles. For the six patients that underwent whole-exome sequencing of whole blood, we also assessed for the presence of other AA-risky non- HLA SNP, including telomeric repeat binding factor 1 ( TERF1 ) (rs3863242) [ 25 ], CTLA4 (rs231775) [ 26 ], PDCD1 (rs36084323) [ 27 ], IFNG (rs2430561) [ 28 ], FAS (rs1800682) [ 29 ], and FOXP3 (rs3761548) [ 30 ]. The only one that was detected was the CTLA4 p.T17A (rs231775) SNP, with five of the six cases carrying the AG genotype and Case 9 carrying the GG genotype that has been reported as AA-risky in Chinese Han [ 26 ] but not in Caucasians [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Case 4 carried both AA-risky and -protective HLA alleles, whereas Case 11 (i.e., the patient suffering a hepatitis-associated AA subtype) only carried AA-protective alleles. For the six patients that underwent whole-exome sequencing of whole blood, we also assessed for the presence of other AA-risky non- HLA SNP, including telomeric repeat binding factor 1 ( TERF1 ) (rs3863242) [ 25 ], CTLA4 (rs231775) [ 26 ], PDCD1 (rs36084323) [ 27 ], IFNG (rs2430561) [ 28 ], FAS (rs1800682) [ 29 ], and FOXP3 (rs3761548) [ 30 ]. The only one that was detected was the CTLA4 p.T17A (rs231775) SNP, with five of the six cases carrying the AG genotype and Case 9 carrying the GG genotype that has been reported as AA-risky in Chinese Han [ 26 ] but not in Caucasians [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other smaller studies on some of these patients have revealed genetic predispositions for AA in FAS/FASL system, GSTM1 and GSTT1 and different HLA alleles [32][33][34]. Similarly, low fraction of PNH positivity may also point toward underlying non-immune mechanisms in the disease pathogenesis.…”
Section: Consanguinity and Genetic Factorsmentioning
confidence: 89%
“…9 Because the allele G of FAS c.671A > G was previously associated with lower apoptosis of damaged cells, 13 these results were not expected by us. However, activation of FAS/FASL was described as an important mechanism in erythroid maturation 50 and regulation of red blood cell homeostasis, 51 and Rehman et al 52 observed that G allele of FAS c.-671A > G increased aplastic anemia risk. Moreover, deletion of FAS in lymphocytes caused lymphopenia in mice, 53 suggesting that FAS expression in lymphocytes is required for their survival and/or proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…G was previously associated with lower apoptosis of damaged cells, 13 these results were not expected by us. However, activation of FAS/FASL was described as an important mechanism in erythroid maturation 50 and regulation of red blood cell homeostasis, 51 and Rehman et al 52 observed that G allele of FAS c.-671A . G increased aplastic anemia risk.…”
Section: Discussionmentioning
confidence: 99%